VALIDATION OF ASESULFAM ANALYSIS METHODS IN SWEETENER PRODUCTS AND CONTRIBUTION TO EXPOSURE OF DIABETIC PATIENTS AT THE KIARA HUSADA CLINIC BANDUNG - Aulia Rahman, Adam
Food additives (FA) are components added to food to influence the nature or form of food. Acesulfame is one of the FA belongs to the functional class of sweeteners permitted in several categories of food products, including table top sweeteners. The aims of this study were to obtain an analytical method for determination of acesulfame in table top sweetener, data on acesulfame levels and estimation of acesulfame exposure in diabetic patients from this product. The validation parameters determined, include linearity, precision, accuracy, limit of detection (LOD), and limit of quantification (LOQ) of analytical method using high performance liquid chromatography (HPLC). The precision and accuracy of the method are expressed as relative standard deviation (RSD) and percent of recovery of the determination of the standard added in the range of 80-120% of the actual concentration of acesulfame in the sample. The LOD and LOQ of the method were statistically calculated from the calibration curve. Exposure assessment was carried out by filling out questionnaires by diabetic patients as respondents using the food recall method. The results showed, the calibration curve of acesulfame has the equation of Y = 0.6654 X-0.002 and R2 value of 0.9991, relative standard deviation in the range of 0.38 - 3.9 %, percent recovery in the range of 91.2 - 94.8 %, as well as LOD and LOD of 1.54 ?g/mL and 4.68 ?g/mL, recpectively. Acesulfame exposure from products A and B were respectively 0.11 and 0.24 mg/kg bw/day, equivalent to 0.40 and 0.24% of the acceptable daily intake (ADI) of acesulfame of 15 mg/kg bw/day. Based on the overall results, it colud be concluded that the method for the determination of acesulfame in table top sweetener products was successfully obtained, the levels of asulfame in the product were 4.24 and 9.28 mg/g, and exposure of acesulfame in diabetic patients was not geater than its ADI value.